2022
DOI: 10.1007/s12024-021-00455-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Covid-19 lockdown on sexual assault cases in Eastern Denmark – a retrospective clinical forensic study

Abstract: To explore if the shutdown of Danish nightlife during the Covid-19 pandemic caused a decrease in the number of clinical forensic examinations of victims of sexual assault in Eastern Denmark. Secondarily, to investigate, if there was a change in criminological characteristics, e.g. scene and time of crime, relation to the perpetrator and the proportion of possible drug-facilitated sexual assaults. 130 case files from clinical forensic examinations of individuals of alleged sexual assault in the period 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…Interestingly, its findings show how DFSA was more prevalent when violence occurred in public places or in houses different from the one of the victims, and women aged 18–25 were considered the group at higher risk of victimization [ 41 ]. In a study conducted in Denmark [ 42 ] 70% of all victims of DFSA between 2019 and 2020 were between the age of 15 and 25 and during 2020 62% of the overall victims of DFSA had voluntarily consumed alcohol, a figure lower than our results.…”
Section: Discussioncontrasting
confidence: 89%
“…Interestingly, its findings show how DFSA was more prevalent when violence occurred in public places or in houses different from the one of the victims, and women aged 18–25 were considered the group at higher risk of victimization [ 41 ]. In a study conducted in Denmark [ 42 ] 70% of all victims of DFSA between 2019 and 2020 were between the age of 15 and 25 and during 2020 62% of the overall victims of DFSA had voluntarily consumed alcohol, a figure lower than our results.…”
Section: Discussioncontrasting
confidence: 89%
“…One crime that has been notably absent from this list is an in-depth examination of sexual assaults. While a number of researchers have explored the impact of the COVID-19 pandemic on the delivery of support services and health care to survivors of sexual assault ( Engleton, Goodman-Williams, Javorka, Gregory, & Campbell, 2022 ; Munro-Kramer, Cannon, Scheiman, St Ivany, & Bailey, 2021 ; Wood et al, 2022 ), few studies have reported more than general trends, such as the decline in sexual assaults and other violent crimes during precautionary lockdowns ( Bidstrup, Busch, Munkholm, & Banner, 2022 ; Payne, Morgan, & Piquero, 2022 ; Shen, Fu, & Noguchi, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%